Evasion of tipping in complex systems through spatial pattern formation - Rietkerk, Max; Bastiaansen, Robbin; Banerjee, Swarnendu; van de Koppel, Johan; Baudena, Mara; Doelman, Arjen (Science (American Association for the Advancement of Science), 2021)
The concept of tipping points and critical transitions helps inform our understanding of the catastrophic effects that global change may have on ecosystems, Earth system components, and the whole Earth system. The search for early warning indicators is ongoing, and spatial self-organization has been interpreted as one such signal. Here, we review how spatial self-organization can aid complex systems to evade tipping points and can therefore be a signal of resilience instead. Evading tipping points through various pathways of spatial pattern formation may be relevant for many ecosystems and Earth system components that hitherto have been identified as tipping prone, including for the entire Earth system. We propose a systematic analysis that may reveal the broad range of conditions under which tipping is evaded and resilience emerges.